PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN â€œE LEARNINGâ€ DiTENGAH PANDEMI COVID-19 KELAS VIII PERSIAPAN MTS N 3 PADANGSIDIMPUAN - Lili Nur Indah Sari (FORUM PAEDAGOGIK, 2021)
This research is a quasi-experimental research, with a quantitative approach to finding data in the form of numbers, namely the results of the pre-test and post-test. One of the information technologies that can be used as a learning medium is by using e-learning. E-learning is an innovation that can be utilized in the learning process, not only in the delivery of learning material, but also changes in the abilities of various student competencies. The instrument used in this study was a test. The test instruments include pre-test and post-test. The pre-test includes a set of prerequisite material knowledge in the form of descriptive questions and the post-test includes a mathematics learning outcome test. Based on the results of the analysis of hypothesis testing carried out using the t-test at a significance level of 0.05, the sig value is obtained. (2-tailed), which is equal to 0.000, which is smaller than the significance level of 0.05. So, it can be concluded that there is a significant increase in student learning outcomes taught by e-learning learning during the Covid 19 pandemic.Key words: learning outcomes; e learning; covid 19